(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Public and community health is a critical section for medical students during the training program in universities as well as in the future work as medical staff. Important lessons could be learnt from prevention and control efforts of Covid-19 pandemic. This study examined the roles and attitudes of medical students who actively participated in Covid-19 prevention and control activities in Vietnam. Methods: A survey was conducted among 1175 medical students via questionnaires to assess their satisfaction and attitudes toward their participation. Results: It indicated high satisfaction with the preparation and assurance, including specialized training and knowledge preparation. Collaborative efforts between medical students with healthcare staff, local authorities, or patients were viewed positively. Medical students played a significant role in alleviating healthcare system pressure, promptly supporting patients as well as reducing patients’ anxiety. Their participation facilitated knowledge reinforcement, the acquisition of clinical skills, and the development of communication abilities. Furthermore, medical students demonstrated an increased awareness and sense of responsibility towards the community, exhibiting a positive attitude toward their involvement and a willingness to engage in similar situations in the future. Conclusions: These findings emphasize the positive impact of involving medical students in pandemic response efforts and the need to address their concerns for future initiatives. The outcomes of this study contribute to the understanding of the valuable role that medical students can play in public health emergencies and provide insights for educational and healthcare institutions on effectively exploring their potential.